3-dimensional intracardiac echocardiography for structural heart interventions - Ho, Edwin C.; Assafin, Manaf; Sugiura, Tadahisa; Granada, Juan F.; Chau, Mei; Latib, Azeem (Frontiers in Cardiovascular Medicine, 2023)
New generation 3-dimensional matrix array intracardiac echocardiography catheters have become commercially available recently, increasing image plane options compared to 2-dimensional and older generation 3-dimensional intracardiac echocardiography catheters. They are beginning to play an important role in structural heart interventions, especially for transcatheter tricuspid interventions, due to advantages in some situations that increase image quality over transesophageal echocardiography.